PENGEMBANGAN MEDIA PEMBELAJARAN SAINS BIG SCRAPBOOK TEMA 7 SUBTEMA 3 PADA SISWA KELAS IV SD PATRA DHARMA TARAKAN - Lili Rahmawati; Kartini Kartini; Agustinus Toding Bua (Biopedagogia, 2021)
This study was intended to develop a big scrapbook as a learning media and to determine the feasibility and level of students’ interest in learning media developed in thematic learning on theme 7 sub-thema 3, the beauty of unity and oneness in my county fo the fourth grade students of SD Patra Dharma Tarakan. This type of research was a research and development (RD) which aimed at producing a product using the ADDIE development model which consisted of five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The data were collected through observation, interview, student’ initial questionnaire, validation, student’ interest questionnaire, and documentation. The resulted product of big scrapbook media consisted of 22 sheets and 42 pages which were made in art paper with A3 paper size (29 x 42 cm), colorful cover paper, and origami patterned paper. The results of validation from media expert was 84%, material expert was 100%, and practitioner was 94%. The students’ interest from the initial product trials was 91.33%, and the usage trials were 93.2%. The validation of a media expert, material expert, and practitioner expert showed that the big scrapbook learning media was suitable for the learning process. The results of the students’ interest regarding to the learning media in the initial product trials and usage trials showed that the level of students’ interest in the big scrapbook learning media was very interested. Keywords:  Learning media, Big Scrapbook.